Pedagogical Experiences of Islamic Education (PAI) Teachers in Instilling Islamic Values among Students with Special Needs at MA Al-Whatoniyah Pusat, Klender, East Jakarta: Pengalaman Pedagogis Guru PAI dalam Menanamkan Nilai-Nilai Keislaman pada Anak Berkebutuhan Khusus di MA Al-Whatoniyah Pusat, Klender, Jakarta Timur - Shulu Khiyah; Yudril Basith (Bestari: Jurnal Pendidikan dan Kebudayaan, 2026)
T The purpose of this study is to examine the strategies and challenges faced by Islamic Religious Education teachers in instilling Islamic values in children with special needs. This study employs a qualitative method using a grounded theory approach. Data were collected through observation, interviews, and documentation. Data analysis in this study was conducted through the grounded theory stages, which include open coding, axial coding, and selective coding. Data validity was ensured through triangulation of techniques and sources. The results of the study indicate that teachers’ pedagogical experiences are implemented through adaptive and inclusive strategies, such as storytelling and modeling, daily religious practices, personalized educational communication, peer tutoring, classroom management, and assessments tailored to students’ abilities. However, several challenges exist, including limited teacher training, diverse student characteristics, and constraints regarding time and supporting facilities.